2011
DOI: 10.1111/j.1468-0432.2011.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional Sensibilities in Analysing Inequality Regimes in Public Sector Organizations

Abstract: Using Acker's conceptual framework of inequality regimes, this article explores the experiences of Bangladeshi, Caribbean and Pakistani women working in three parts of the public sector: health, local government and higher education. Our concern is to investigate how inequality regimes are sustained, despite the existence in the public sector of more sophisticated policy development and stronger legal duties than in the private sector. Drawing on interviews with managers and with women employees, the study dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(168 citation statements)
references
References 20 publications
7
155
0
6
Order By: Relevance
“…The DREI(C) method underpins this methodological approach, and guides theoretical explanation (Bygstad & Munkvold 2011;Danermark et al 2002). It requires describing (Byrne 2006;Healy et al 2011) and contrastive (Lawson 2003;Mussell 2016) analytical techniques to inform our comparative case method (Kaarbo & Beasley 1999) and assist in retroduction.…”
Section: Methodology and Method: Cr Intersectional Feminist Contrastimentioning
confidence: 99%
See 1 more Smart Citation
“…The DREI(C) method underpins this methodological approach, and guides theoretical explanation (Bygstad & Munkvold 2011;Danermark et al 2002). It requires describing (Byrne 2006;Healy et al 2011) and contrastive (Lawson 2003;Mussell 2016) analytical techniques to inform our comparative case method (Kaarbo & Beasley 1999) and assist in retroduction.…”
Section: Methodology and Method: Cr Intersectional Feminist Contrastimentioning
confidence: 99%
“…Simultaneously, coverage of successful digital entrepreneurs permeates UK online, news and print media (Bravo 2016;Bownass 2016;Urwin 2017;Walker 2016) while leading digital platforms encourage such activity. Despite this, relatively sparse evidence exists regarding the effects of participating in digital entrepreneurship, particularly for marginalised and disadvantaged people (Sussan & Acs 2017;Martinez Dy et al 2017) who are more likely to experience structural challenges to employment (Berry & Bell 2012;Healy et al 2011). The rapid growth of online trading, a key aspect of digital entrepreneurship, is as yet underexplored within the business and management literature (Chandra & Coviello 2010;Nambisan 2016;Williams 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recruitment and selection practices are permeated by gender, ethnicity, age, and other stereotypes, and these stereotypes contribute to the persistence of inequality (Healy et al 2011). Studies on discrimination in recruitment and hiring (e.g., Beattie and Johnson 2012;Rooth 2010) have shown that recruiters' attitudes and perceptions of stereotypes often operate at an unconscious level.…”
Section: Recruitment As An Organizing Process Producing Inequalitymentioning
confidence: 99%
“…This might partly explain why official human resources policy at the organizational level and equality acts and legislation at the societal level have not guaranteed gender-, ethnicity-, and age-neutral recruitment and selection practices (Acker 2009, pp. 208-209;Healy et al 2011).…”
Section: Recruitment As An Organizing Process Producing Inequalitymentioning
confidence: 99%
“…Los resultados sugieren que, de forma individual, ni la gestión de la diversidad ni las iniciativas legales son suficientes para garantizar una justicia social efectiva pero, en contextos de desigualdades durables, resulta un primer paso necesario. (Tilly, 1999) and to the study of inequality regimes in work settings (Acker, 2006;Healy;Bradley;Forson, 2011). Our interest in the comparison with the USA experience has a number of reasons.…”
unclassified